2013
DOI: 10.1074/jbc.m113.459768
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structural Insight into Human Variegate Porphyria Disease

Abstract: Background: Defects in the human protoporphyrinogen oxidase (PPO) causes the variegate porphyria (VP) disease. Results: The activity of 44 clinically reported VP-causing mutants have been accurately predicted. Conclusion: A quantitative understanding into the molecular basis of VP by PPO mutation was established. Significance: The quantitative insight into VP should be helpful for the diagnosis, precaution, and treatment of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 48 publications
0
54
0
1
Order By: Relevance
“…One example includes mutations in the human protoporphyrinogen oxidase (hPPO) gene which are responsible for the dominantly inherited disorder variegate porphyria (VP). Two missense mutations (R59Q and R59G) were investigated in a recent work 130 where MD modeling revealed that these mutations affect the catalytic activity of hPPO by changing its ability to sample different conformations. Analysis of mutation H101Q in the CLIC2 protein demonstrated that this mutation restricted the mobility of the N-terminal domain and prevented the conformational change presumed to be required for entering of CLIC2 into the membrane.…”
Section: Effect Of Mutations On Conformational Dynamicsmentioning
confidence: 99%
“…One example includes mutations in the human protoporphyrinogen oxidase (hPPO) gene which are responsible for the dominantly inherited disorder variegate porphyria (VP). Two missense mutations (R59Q and R59G) were investigated in a recent work 130 where MD modeling revealed that these mutations affect the catalytic activity of hPPO by changing its ability to sample different conformations. Analysis of mutation H101Q in the CLIC2 protein demonstrated that this mutation restricted the mobility of the N-terminal domain and prevented the conformational change presumed to be required for entering of CLIC2 into the membrane.…”
Section: Effect Of Mutations On Conformational Dynamicsmentioning
confidence: 99%
“…Unfortunately, there are no crystal structures with a bound substrate or product that would help to identify essential interactions between the tetrapyrrole and the enzyme. However, there are structures with a bound inhibitor, which allowed in silico modeling of substrate binding (210)(211)(212)264). Based upon kinetic studies with a tritium-labeled substrate, it was proposed that three meso-carbon hydride ions are removed from the same surface of the tetrapyrrole in a sequential fashion with the concomitant removal of the NH proton (265).…”
Section: Prokaryotic Heme Biosynthesismentioning
confidence: 99%
“…The result provided structural evidence for protogen IX binding place in PPO. Therefore, we have explored the binding mode of protogen IX in h PPO through molecular simulation and site‐directed mutagenesis study ,. Interestingly, the binding mode of protogen IX in h PPO was different from the one in mt PPO proposed by Koch et al ., which showed the methylene bridge atom C5, instead of C20 (see Scheme ), was close to the N5 atom of FAD.…”
Section: Methodsmentioning
confidence: 93%